Finding balance: understanding the energetics of time‐restricted feeding in mice. (13th December 2022) - Gallop, Molly R.; Tobin, Selene Y.; Chaix, Amandine
Abstract: Over the course of mammalian evolution, the ability to store energy likely conferred a survival advantage when food became scarce. A long‐term increase in energy storage results from an imbalance between energy intake and energy expenditure, two tightly regulated parameters that generally balance out to maintain a fairly stable body weight. Understanding the molecular determinants of this feat likely holds the key to new therapeutic development to manage obesity and associated metabolic dysfunctions. Time‐restricted feeding (TRF), a dietary intervention that limits feeding to the active phase, can prevent and treat obesity and metabolic dysfunction in rodents fed a high‐fat diet, likely by exerting effects on energetic balance. Even when body weight is lower in mice on active‐phase TRF, food intake is generally isocaloric as compared with ad libitum fed controls. This discrepancy between body weight and energy intake led to the hypothesis that energy expenditure is increased during TRF. However, at present, there is no consensus in the literature as to how TRF affects energy expenditure and energy balance as a whole, and the mechanisms behind metabolic adaptation under TRF are unknown. This review examines our current understanding of energy balance on TRF in rodents and provides a framework for future studies to evaluate the energetics of TRF and its molecular determinants. Abstract : Whole‐body energy balance based on daily phase of eating and diet composition. This figure summarizes the current literature on energy balance under different feeding regimens with each tile of the figure independently representing a unique feeding intervention. The "teeter‐totter" In each tile represents the whole‐body energy balance; energy intake (EI) is represented on the left as food pellets, and energy expenditure (EE) is represented on the right side of each scale as a flame. Higher levels of EI or EE are represented as being heavier and tilting the scale in their respective direction. The ensuing effects on body weight are shown on the right side of each tile.